IMPLEMENTATION OF MAQĀṢID AL-QUR’ĀN IN ACEH’S QANUN: TOWARD A FRAMEWORK OF SHARIA LEGISLATION AND SOCIAL MAṢLAḤAH - Mujahidin, Sultan (Sekolah Tinggi Agama Islam Sadra, 2026)
Aceh, as a province with special autonomy, has implemented Islamic Sharia through regional regulations known as qanun. However, its implementation is frequently criticized for being entangled in legalistic and punitive formalism. This research aims to analyze the implementation of maqāṣid al-Qur’ān within the Aceh Qanun and its transformation toward substantive justice. Diverging from previous studies that focused primarily on classical maqāṣid al-sharī‘ah (the protection of the five essential elements), this study employs the more universal and inclusive paradigm of maqāṣid al-Qur’ān as an analytical framework. The methodology is qualitative-descriptive, utilizing exegetical literature—specifically Tafsir Al-Mishbah—and contemporary maqāṣid theories as primary sources to examine the Aceh Qanun as the object of research. The findings reveal a significant gap between the idealistic message of the Qur’an—which emphasizes mercy, social justice, and human dignity—and the reality of qanun texts, which remain predominantly punitive. This study identifies that the Qanun Jinayat, Qanun Maisir, and Qanun Syiar Islam require methodological deconstruction to shift their focus from mere external compliance to substantive welfare. As a solution, this research proposes “The Integrated maqāṣid al-Qur’ān Framework” for future legislative drafting, based on value-based ontological analysis, a multidisciplinary systems approach, and social maṣlaḥah indicators. These findings underscore the necessity of revitalizing the paradigm of Islamic law in Aceh, moving from a mere instrument of social control toward a humanistic and dignified model of human empowerment in accordance with the universal vision of the Qur’an.